Disputatio ordinaria and disputatio de quodlibet. Medieval Models of Contemporary Didactics of Political and Legal Doctrines - Skomiał, Jakub (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Referring to the seminar entitled “Doctrinal study of the Star Wars universe. Star Wars. Republic versus Empire” held a few years ago with the participation of the Department of Political and Legal Doctrines of the University of Lodz and students, the article considers the potential of using models drawn from late medieval universities in contemporary academic didactics. Particular attention was paid to disputes held with active participation of students, the themes of which could be indicated either by the master (disputatio ordinaria) or by anyone else (disputatio de quodlibet). The latter required from the master to demonstrate their comprehensiveness and authority.